Kampanye Minimalist Lifestyle Bagi Mahasiswa Di Kota Padang - Fajriah Utami; Dwi Mutia Sari (Universitas Katolik Widya Karya Malang, 2023)
Consumption is an activity aimed at reducing or utilizing a product, whether it is a physical product or a service. Along with the times, the level of consumption is getting higher, especially among students. This increase in consumption activity is based on the attractiveness of an item, thus providing satisfaction to consumers. If consumption cannot be controlled, it will lead to consumptive behavior. Therefore the authors designed a minimalist campaign to reduce the amount of consumption and chose to optimize the use of goods to make them more effective and useful. This design uses the Research and Development (R&D) 4-D model with the stages: define, design, develop and disseminate. In the process of solving the problem the writer applies 5W+1H data analysis (what, where, when, who, why and how). The main media for this design is the Instagram feed as a medium for voicing a minimalist lifestyle campaign.